ANALISIS SEMIOTIK PESAN PERJUANGAN PADA FILM 3 SRIKANDI KARYA IMAN BROTOSENO - Suriadi .; Sulih Indra Dewi (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstrack : The film "3 Srikandi" is a film that recounts the historical record of the struggle of Indonesian athletes who managed to bring home the first silver medals for Indonesia. Since the participation of Indonesia in the Olympic Games in 1952, Indonesia was just managed to bring a medal from the archery sport. This study aimed to determine the struggling messages and how the analysis of semiotics contained in “3 Srikandi”. This type of research is qualitative research with Roland Barthes semiotics analysis approach. Roland Barthes developed the semiotics theory which is often known by the two-stage significance of denotation and connotation. The results of the analysis from several scenes were: 1) How the struggling messages shown in the film “3 Srikandi”, from the home setting, training field, field match and characterizations. 2) The semiotic analysis of the struggling messages the film was tough against suffering, sacrifice, nationalism, realizing hope, hard training, delayed victory, power against the pain, and the struggle behind the success of 3 Srikandi. In addition to the messages of struggling in the movie 3 Srikandi, this film also told about the problems of athletewelfare, it is expected to be a concern for the development of sports, especially the attention of the government. Keywords: Semiotics Analysis, Struggling Message, Film 3 Srikandi. Abstrak: Film “3 Srikandi” merupakan film yang menceritakan catatan sejarah perjuangan para atlet Indonesia yang berhasil membawa pulang medali perak pertama untuk indonesia. Sejak keikutsertaan Indonesia di olimpiade Sea Games tahun 1952, Indonesia baru berhasil membawa medali di cabang olahraga panahan. Penelitian ini bertujuan untuk mengetahui pesan perjuangan dan bagaimana analisis semiotik yang terdapat dalam film 3 Srikandi. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan Semiotika Roland Barthes. Roland Barthes mengembangkan teori semiotika yang sering dikenal dengan signifikasi dua tahap yaitu denotasi dan konotasi. Hasil dari analisis yang telah dilakukan oleh peneliti pada beberapa scene, 1) Bagaimana pesan perjuangan ditampilkan dalam film 3 Srikandi diantaranya dari setting rumah, lapangan latihan, lapangan pertandingan dan penokohan. 2) Hasil analisis semiotika pesan perjuangan dalam film 3 Srikandi adalah tangguh melawan penderitaan, rela berkorban, sikap nasionalisme, mewujudkan harapan, latihan keras, kemenangan yang terunda, melawan rasa sakit, dan perjuangan dibalik keberhasilan 3 Srikandi. Selain pesan perjuangan yang terdapat pada film 3 Srikandi, film ini juga menceritakan permasalahan tentang kesejahteraan para atlet, hal ini diharapkan menjadi perhatian untuk perkembangan olahraga, khususnya perhatian dari pemerintah. Kata Kunci: Analisis Semiotika, Pesan Perjuangan, Film 3 srikandi